บทบาทสตรีในรามเกียรติ์ : ศึกษาเปรียบเทียบนางสีดาของอินเดียและไทย - หรรษา ติ่งสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The objective of the study is to compare the roles of women in Ramakien in Thailand and Ramayana in India through the character of Sita as daughter wife and mother. Cultural Diffusion, Literature and Society, and Feminist theories are employed in the analysis. The study adopted qualitative method by analizing two main literary works: Ramakien written by king Rama I and Ramayana written by Valmiki and translated by suporn Pholcheewin. The result of the study indicates that the women’s roles as daughter, wife and mother in India and Thailand are similar. This is because of cultural diffusion which brought patriarchy from India to Thailand. The concept of patriarchy influenced all classes of people. This main factor allows men to have power over women. Hence women are suppressed by men. This causes gender segregation and sexual domination in many instances. But, in case of Sita, She was not totally dominated by men. She refused to follow Rama’s order to go back to him and she also gave order to Laxman. However the difference in women’s role in India and Thailand through the analysis of Sita lies in quality of live, social values, tradition, norm, and religious belief of Buddhism and Hindu.